The Effect of Product Quality and Price Discounts on Word of Mouth and Purchasing Decisions at Esteh Indonesia - Ramaddini, Putri Aulia; Silitonga , Parlagutan (Indonesian Journal Publisher, 2024)
This study aims to determine the effect between product quality and price discounts on word of mouth (WOM) and purchasing decisions at Esteh Indonesia. The subjects of this survey were all Esteh Indonesia consumers. In this study, 250 respondents were involved, selected by accidental sampling method, which is a sampling technique based on the coincidence or availability of consumers in a location. Data was collected through the distribution of questionnaires. Data analysis was conducted using Structural Equation Modeling (SEM) using Smart-PLS software. The results showed that product quality has a significant impact on WOM, but is not proven to have a significant influence on purchasing decisions. In addition, price discounts are also proven to influence and have a significant impact on WOM and purchasing decisions. WOM is proven to have a significant impact on purchasing decisions, which is influenced by credibility, personal relevance, emotional connection, group influence, and relatively low costs. Because of this, WOM is one of the effective marketing strategies in influencing consumer behavior.